Extra Curriculum Activity Participation and Employability Prospects of Undergraduates - Babajide, Sanni Adewale; Adesina, Raji Ismail; Rahmon, Tella Adeniran (ESUT JOURNAL OF SOCIAL SCIENCES, 2025)
Graduate employability continues to pose a major challenge within Nigerian higher education, with many university graduates lacking the competencies demanded by contemporary labour markets. This study investigates the employability prospects of undergraduates at the University of Ibadan and the influence of their participation in extracurricular activities. Employing a descriptive survey of the correlational design, data were gathered from 612 undergraduates through a structured questionnaire. Results revealed that students rated their employability skills relatively low, particularly in the areas of critical thinking, professional communication, and digital presence. Conversely, high levels of participation were reported in extracurricular activities such as sports, student clubs, and campus politics, though engagement in entrepreneurship was limited. A statistically significant moderate positive correlation was found between extracurricular participation and employability prospects (r = .466, p < .001). Further analysis using simple linear regression showed that extracurricular participation significantly predicted employability prospects, (F(1;610) = 168.76, p < .001, Adj. R² = .215). The study concludes that structured extracurricular engagement contributes meaningfully to students’ perceived employability and recommends institutional integration of employability skills training and digital competence development within and beyond the curriculum.